Does Botulinum Toxin A Treatment Enhance the Walking Pattern in Idiopathic Toe-Walking? - Sätilä, Heli; Beilmann, Anneli; Olsén, Päivi; Helander, Heli; Eskelinen, Mari; Huhtala, Heini (Neuropediatrics, 2016)
Objective We conducted a randomized controlled trial to evaluate whether a combination of repeated botulinum toxin A (BTX-A) and conservative treatment is more effective in decreasing toe-walking than conservative treatment alone at 24 months follow-up.Patients and Methods Children between 2 and 9 years of age were randomized either into the conservative (CO) or botulinum treatment (BTX) group. The treatment in the CO group consisted of firm shoes, night splints, a home stretching program and physiotherapy. The BTX arm had all the same conservative treatments added with calf muscle BTX-A injections repeated in 6 months intervals if needed. Change in toe-walking pattern, ankle range of movement (ROM), and overall function were assessed at baseline and 6, 12, 18, and 24 months posttreatment.Results A total of 30 toe-walkers participated: 14 in CO and 16 in BTX group. At 24 months, all children in the BTX group and 85% in the CO group evaluated by the blinded physiotherapist (p = 0.065), 75% in the BTX group and 70% in the CO group graded by the research physiotherapist (p = 0.730), and 50% in the BTX group and 54% in the CO group reported by the parents ceased toe-walking (p = 0.837). The most prominent change was noted during the 1st year. The BTX group seemed to reach the goal earlier. No significant differences between the treatment groups in function or in ankle ROM ensued.Conclusion Adding BTX injections did not significantly enhance the goal to walk either flat foot or with heel strike at 24 months posttreatment.
Keywords: idiopathic toe-walking; toe-walking; botulinum toxin A; conservative treatment